Analysis of a brown earth palaeosol and derived sediments associated with a Mesolithic pit, a Late Neolithic – Early Bronze Age burnt mound and an Early Bronze Age burnt mound on Exmoor, UK. (February 2021) - Carey, Chris; Macphail, Richard; Bray, Lee; White, Hayley; Scaife, Rob
Highlights: Pre-peat sediment sequences associated with dated archaeological features are analysed. Late Neolithic – Early Bronze Age colluvial soil erosion defines human landscape impacts. Human impacted slaked and trampled soils/sediments are discovered underneath two burnt mounds. No evidence of podzolisation was found in the soils/sediments under either burnt mound. Anthracological analysis of the burnt mounds demonstrates use of Oak and Alder trunk wood in the EBA. Abstract: The deforestation of upland areas in southwest Britain during the mid-Holocene has become an archaeological narrative, derived from the analysis of pollen within upland peat deposits. The transition of these environments from brown earth soils supporting temperate deciduous woodland, into the now familiar podzolic peat mire landscapes is seemingly associated with abandonment of the uplands in late prehistory. The prehistoric archaeological records of these landscapes are rich and significant questions remain unanswered about prehistoric societies and their role in the environmental transition of these upland systems. Despite these rich archaeological records and detailed palaeoecological studies, the geoarchaeological study of the pre-peat sediments has remained somewhat limited. This paper provides the analysis of a Mesolithic heated pit infilled with a brown earth soil, and the pre-monument deposit sequences at two burnt mounds dating to the Late Neolithic – Early Bronze Age. The analysis of these dated sequences provides an increased understanding of these environments prior to the transition of these areas into stagnogley podzols and identifies considerable human impacts, indicating that anthropogenic activities were linked to important processes negatively impacting on soils in these upland areas and contributing to their degradation.